2017 IEEE International Symposium on Multimedia (ISM) 2017
DOI: 10.1109/ism.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Country Similarity in Terms of Music Taste, Cultural, and Socio-economic Factors

Abstract: Abstract-Considering the cultural background of users is known to improve recommender systems for multimedia items. In this work, we focus on music and analyze user demographics and music listening events in a large corpus (120,000 users, 10 9 events) from Last.fm to investigate whether similarity between countries in terms of cultural and socio-economic factors is reflected in music taste. To this end, we propose a tag-based model to describe the music taste of a country and correlate the resulting music prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Although positions are fairly stable over the years, if anything, clusters of countries seem to consolidate, being these three groups more clearly discernible in 2020 than in 2017. At first sight, these results are consistent with general notions of cultural, geographical, and linguistic distance which elsewhere have been proved to be the main determinants of music taste similarities between countries (Pichl et al 2017;Schedl et al 2017;Moore et al 2014).…”
Section: Resultssupporting
confidence: 87%
“…Although positions are fairly stable over the years, if anything, clusters of countries seem to consolidate, being these three groups more clearly discernible in 2020 than in 2017. At first sight, these results are consistent with general notions of cultural, geographical, and linguistic distance which elsewhere have been proved to be the main determinants of music taste similarities between countries (Pichl et al 2017;Schedl et al 2017;Moore et al 2014).…”
Section: Resultssupporting
confidence: 87%
“…The work at hand differentiates from related work in several aspects. First, although music preferences vary across countries, several studies (e.g., Moore et al, 2014 ; Pichl et al, 2017 ; Schedl et al, 2017 ; Bauer and Schedl, 2019 ) have shown similarities in music preferences between countries, typically identified with clustering approaches. Yet, to the best of our knowledge, the work at hand is the first one to integrate information on country similarities into the music recommendation approach.…”
Section: Conceptual Background and Related Workmentioning
confidence: 99%
“…Our sample focused only on participants situated in the United States. Recent work showed that there are cultural differences in music consumption (e.g., [27,37,82,83,90]). Hence, cultural differences may also play a role in taxonomy usage and category preferences.…”
Section: Limitations and Future Workmentioning
confidence: 99%